Impact of Socio-demographic Factors on Cyber Addiction and Cyberbullying Among Adolescents in Nigeria - Olubode, Henry; Akinyemi, Elizabeth; Omolayo, Benjamin; Umoru, Thaddeus; Olawa, Babatola (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
The internet was developed to foster easy access to information but has been abused in terms of addiction and bullying. The main objective of this study was to assess cyber addiction and cyberbullying among adolescents in public tertiary institutions. The sample of the study consisted of 400 adolescents from 4 public tertiary institutions in Nigeria. Using an ex-post facto research design, the results indicate that 0.7% of adolescents were severe internet addicts, 26.8% were normal users, 42.5% were mildly addicted, and 30% were moderately addicted to internet use. Regression analysis showed that socio-demographic factors such as age, biological sex, religious affiliation, the institution of study, years of using the internet, and internet device usage jointly predicted cyber addiction and cyberbullying. Religious affiliation and years of using the internet independently predicted cyber addiction, while age independently predicted cyberbullying. The research findings revealed the need for monitoring and controlling adolescents' internet activities. Abstrak Internet dikembangkan untuk memfasilitasi akses mudah terhadap informasi, namun banyak disalahgunakan dan menimbulkan kecanduan serta perundungan. Tujuan utama dari studi ini adalah untuk mengetahui kecanduan dan perundungan di dunia cyber kalangan remaja di institusi pendidikan tinggi publik. Sampel penelitian diambil dari 400 remaja dari 4 institusi pendidikan tinggi publik di Nigeria. Dengan menggunakan desain penelitian eks-post facto, hasil penelitian menunjukkan bahwa 0,7% remaja mengalami kecanduan internet yang parah, 26,8% adalah pengguna normal, 42,5% mengalami kecanduan ringan, dan 30% mengalami kecanduan sedang terhadap penggunaan internet. Analisis regresi menunjukkan bahwa faktor-faktor sosiodemografi seperti usia, jenis kelamin biologis, afiliasi agama, institusi studi, tahun penggunaan internet, dan penggunaan perangkat internet secara bersama-sama memprediksi kecanduan cyber dan perundungan cyber. Afiliasi agama dan tahun penggunaan internet secara independen memprediksi kecanduan cyber, sementara usia secara independen memprediksi perundungan cyber. Temuan penelitian ini mengungkapkan perlunya pemantauan dan pengendalian aktivitas internet remaja.